Preparation of herbal hair oil exploring the therapeutic benefits of herbs and its evaluation - Dhiraj Baishya; Ananta Choudhury; Himangshu Deka; Nurjamal Hoque; Rosamund Jyrwa; Jahnabi Sarmah (Creative Pharma Assent, 2024)
Background: Herbal cosmetics, particularly herbal hair oils, have gained popularity due to their perceived efficacy and minimal adverse effects. This study aimed to formulate and evaluate herbal hair oils for promoting hair growth. Methodology: Various herbal extracts, including Coconut, Curry leaves, Amla, Fenugreek, and Onion, were prepared and incorporated into virgin Coconut oil. Phytochemical screening, total flavonoid content, organoleptic evaluation, chemical analysis (acid value, saponification value, specific gravity), stability studies, antioxidant assay (DPPH), antimicrobial assay, sensitivity studies, and in-vivo hair growth activity were conducted. Results: Organoleptic evaluation revealed characteristic odors and colors across formulations. Chemical analysis showed acceptable values for acid value (0.68 - 1.86 mg KOH/g), saponification value (117.87 - 224.27 mg KOH/g), and specific gravity (0.865 - 0.933 g/cm^3). Stability studies over 45 days demonstrated consistent physicochemical properties. The DPPH assay indicated dose-dependent antioxidant activity, with inhibition ranging from 13.8% to 66.5%. Antimicrobial assay showed inhibition zones ranging from 6 mm to 20 mm against Staphylococcus aureus. Sensitivity studies exhibited no adverse reactions. In-vivo hair growth activity demonstrated significant improvements compared to controls. Discussion: The formulated herbal hair oils exhibited promising physicochemical properties, antioxidant activity, antimicrobial efficacy, safety, and hair growth promotion in animal models. These findings suggest their potential as natural remedies for hair care. Conclusion: Herbal hair oils formulated in this study show significant potential for promoting hair growth and addressing hair-related concerns. Whereas, formulation F3 shown significant efficacy across multiple parameters among the formulations. Further research and clinical trials are warranted to validate their efficacy and safety for human use.